A Review of Nonprobability Sampling Using Mobile Apps for Fishing Effort and Catch Surveys. Issue 1 (9th December 2021) - Brick, J. Michael; Andrews, William R.; Foster, John
Abstract: Technology and computational advancements have caused us to rethink data collection and sampling methods that have been the standard for gathering information to guide policy decisions. The availability of new technology such as mobile apps has made using nonprobability samples more attractive because of the speed and low expense that are associated with this approach. We review how the use of nonprobability sampling using mobile apps affects the quality of inferences in fishing effort and catch surveys. We present an approach for evaluating the potential biases that arise from both probability and nonprobability sampling methods. The approach shows that well‐conducted probability samples have major advantages compared with nonprobability samples. We conclude that the application of nonprobability sampling for fishing surveys faces serious challenges and should prove that it is fit for use before being adopted more widely.